A very adult curriculum? How the new BC Education plan reflects the andragogical commitments of adult education - Ralf St. Clair (Adult Education Research Conference, 2018)
Analyzes the recently introduced BC K-12 Curriculum through the lens of andragogy to understand the extent to which the values of adult education have informed policy and practice. Bernstein's code theory is used to frame the discussion.
Keywords: curriculum; sociology of education; andragogy; British Columbia